Study of the Ti/InGaAs solid-state reactions: Phase formation sequence and diffusion schemes. (July 2020) - Bensalem, S.; Ghegin, E.; Boyer, F.; Lábár, J.L.; Menyhárd, M.; Gergaud, P.; Nemouchi, F.; Rodriguez, Ph.
Abstract: The development of Complementary Metal Oxide Semiconductor (CMOS)-compatible contact technology on III–V materials based on Ti for electronics or photonics applications was studied. In this framework, solid-state reactions between Ti thin films (20 nm) and In0.53 Ga0.47 As layers grown on InP substrates were studied from the as-deposited state up to 550  °C using a combination of advanced X-ray diffraction (in-plane reciprocal space mapping), Auger electron spectroscopy and transmission electron microscopy analyses. The phase formation sequence was solved. At low temperature, an amorphous Ti–Ga–As intermixing layer coexists with the Ti film. As of 250  °C, the first crystalline phase to form is Ti 2 Ga 3 . At 300  °C, a new crystalline phase appears, namely TiAs 2 . On the other hand, TiAs and metallic In form at 350  °C and Ti is completely consumed between 450 and 500  °C. The diffusion of the various species lead to the formation of a non-nominal Ga-rich In x Ga 1−x As layer and at 550  °C to the formation of polycrystalline GaAs. Ti was found to be the main diffusing species at low temperature whereas III and V elements are the dominant diffusing species at higher temperatures. The nature of the phases formed above and below the original Ti/InGaAs interface might explain the In accumulation at the interface, the TiAs phase acting as a diffusion barrier.